Avaliação da ecotoxicidade de percolados em áreas de disposição de resíduos na região metropolitana de Natal/RN - Mendonça, Jaísa Marília dos Santos (2010)
Leachates are effluent produced by decomposition of solid waste, they have complex composition and can be highly toxic. Therefore such percolated liquid should be collected and treated properly to avoid environmental contamination of soil and of water bodies. The objective of this study was to evaluate the toxicity through ecotoxicological tests with Ceriodaphnia dubia (Cladocera - Crustacea) of percolated liquids generated in two different systems of municipal solid waste (MSW) disposal in the city of Natal/ RN: A Sanitary Landfill in the Metropolitan Region of Natal/ RN, and in a dump off area. Furthermore, it was evaluated the possible contamination of the underground water of the dump off area. Two monthly samples were taken at four points between the months of May/2009 and January/2010. The Point "A" corresponds to the end of the pond leachate treatment in ASRMN; The Point "B" corresponds to a containment pond at the dump. The Point "C" is an area near one of the cells of the dump off area where the leachate outcrops; The Point "D" stands for an underground water well at the area. The last point, called "E" was sampled only once and corresponds to the slurry produced by temporary accumulation of solid waste in the open area of the dump. The ecotoxicological tests, acute and chronic, followed the ABNT 13373/2005 rules, with some modifications. The samples were characterized by measuring the pH number, the dissolved oxygen (DO), the salinity, BOD5, COD, Cd, Cu, Pb, Cr, Fe, Mg, Ni, and Zn. At Point A, the average number of EC50-48h ranged between 1.0% and 2.77% (v/v), showing a high toxicity of the leachate to C.dubia in all months. To this point, positive correlations were found between the EC50- 48 with precipitation. Negative correlations were found between the EC50- 48h with salinity. At point B there was no response of the acute exposure of organisms to the test samples. At point C the EC50-48h ranged from 17.68% to 35.36% in just two months of the five ones analyzed, not correlated meaning. Point D, the EC50-48h level ranged between 12.31% and 71.27%, showed a negative correlation with, only, precipitation. Although it was observed toxicity of underground water in the Landfill Area, there was no evidence of water contamination by leachate, however, due to the toxic character of this water, additional tests should be conducted to confirm the quality of water that is used for human supply. At point E there was no acute toxicity. These results support the dangers of inappropriate disposal of MSW to water bodies due to the high toxicity of the leachate produced highlighting the necessity of places of safe confinement and a treatment system more effective to it